DINAMIKA GERAKAN TAREKAT DI DAERAH MINORITAS MUSLIM KABUPATEN TAPANULI UTARA - Muhammad Nazar Luthfi Tambunan; Syawaluddin Nasution (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
In today's modern era, everyone continues to develop according to the needs and demands of their life. This occurs both in villages and in urban environments. In realizing human development, there are not a few people who are willing to do anything, even violate existing rules and norms. Islam does not leave him alone in this matter, every Muslim can develop according to the demands of the era in which he is by balancing the spiritual side within him. The tarekat exists as a way for everyone to develop but also to purify themselves and draw closer to the Creator. This can also be seen in North Tapanuli district, an area with minority Muslim adherents that also has the potential to develop like people elsewhere in general. The tarekat is also a balancing way for Muslims in North Tapanuli Regency. This can be seen from the enthusiasm of people to follow the congregation's initiation. However, the contests that were held did not run smoothly and even tended to stagnate. This is interesting to study. How is the dynamics of tarekat in North Tapanuli Regency? and how is the spirit of practice of the tarekat students in North Tapanuli Regency? That's why this research was conducted. This research method is qualitative research by presenting data found by researchers in the field. Data collection tools in this study are observation and interviews. From the results of this study, researchers obtained data that in essence the Muslims of North Tapanuli district were very united in congregating, but due to the insufficient foundation of understanding Shari'a and coupled with the low patience of the students, the development of tarekat spirituality from the students became stagnant. The students also admit that they still communicate with the murshid and carry out the obligatory practices during the students' free time.